Framing Poverty in Lithuanian Community Newspapers: Local Authorities, Community Members and Journalists Communicating Social and Policy Changes - Donauskaitė, Džina (Žurnalistikos tyrimai, 2011)
Community media, as opposed to mainstream newsmedia, is an alternative source of information which plays a facilitative role by encouraging community members to express their interests, to join policy debates, and therefore to give authorities feedback on how ongoing policy changes affect members of communities. Due to high levels of concentration of poverty in Lithuanian rural areas and the start of a social assistance decentralisation program to poor residents in five Lithuanian regional municipalities in 2012, the role of local media in policies concerning poverty reduction has increased. Content analysis of five newspapers that served communities affected by the changes reveals that community members are provided with options to communicate poverty issues through community media. This is an empirical finding which supports the author’s claim, presented in this article, that analytical concept of rhisomatic community media rather than liberal critique of local press (which focuses on negative pressures from market and state institutions erected toward the media), is more useful for assessing deliberation processes in local newspapers. Research results show that while communicating poverty, community members prefer to communicate charity initiatives and not to directly engage in public policy debate. Coverage of policy changes is dominated by local authorities and community media journalists. Images of ‘deserving’ and ‘undeserving‘ poor (often without references to actually existing cases) dominate poverty framing in an attempt to support new cash social assistance distributions. Despite facilitating some non-governmental community-organised poverty reduction initiatives, community media acts collaboratively towards on-going policy changes and fails in empowering the poor of the communities they serve. Keywords: community media, decentralisation, poverty.